Catalyst-loaded micro-encapsulated phase change material for thermal control of exothermic reaction - Tatsuya Takahashi (Nature Portfolio, 2021)
Abstract CO2 methanation is a promising technology to enable the use of CO2 as a resource. Thermal control of CO2 methanation, which is a highly active exothermic reaction, is important to avoid thermal runaway and subsequent degradation of the catalyst. Using the heat storage capacity of a phase change material (PCM) for thermal control of the reaction is a novel passive approach. In this study a novel structure was developed, wherein catalysts were directly loaded onto a micro-encapsulated PCM (MEPCM). The MEPCM was prepared in three steps consisting of a boehmite treatment, precipitation treatment, and heat oxidation treatment, and an impregnation process was adopted to prepare a Ni catalyst. The catalyst-loaded MEPCM did not show any breakage or deformation of the capsule or a decrease in the heat storage capacity after the impregnation treatment. MEPCM demonstrated a higher potential as an alternative catalyst support in CO2 methanation than the commercially available α-Al2O3 particle. In addition, the heat storage capacity of the catalyst-loaded MEPCM suppressed the temperature rise of the catalyst bed at a high heat absorption rate (2.5 MW m−3). In conclusion, the catalyst-loaded MEPCM is a high-speed, high-precision thermal control device because of its high-density energy storage and resolution of a spatial gap between the catalyst and cooling devices. This novel concept has the potential to overcome the technical challenges faced by efficiency enhancement of industrial chemical reactions.